Analysis of Transfer Pricing and Product Selling Prices - burhanuddin, chairul iksan; Amran, Amran; Abdi, Muhammad Nur (Akuisisi : Jurnal Akuntansi, 2022)
The purpose of this study is to understand the transfer and product price rates at PT Suri Tani Pemuka.The information presented in this study comes from processes of observation and data collection followed by analysis.This type of research is quantitative, but another type of research is later described that includes information on transfer and product price costs. This study was conducted at PT. Suri Tani Pemuka from 2020 to 2021. Data collection methods include observational techniques, in-depth interview processes, and documentation of findings to allow for visual evaluation of the results.  The results of this study indicate that there are differences in how businesses set their prices using mark-up pricing and variable costing, and that there are differences between prices when businesses do not include non-production costs when setting prices for their products